Gravity’s effect on biology - Narayanan, S. Anand (Frontiers in Physiology, 2023)
Gravity is a fundamental interaction that permeates throughout our universe. On Earth, gravity gives weight to physical objects, and has been a constant presence throughout terrestrial biological evolution. Thus, gravity has shaped all biological functions, some examples include the growth of plants, the structure and morphology of biological parts in multicellular organisms, to its effects on our physiological function when humans travel into space. Moreover, from an evolutionary perspective, gravity has been a constant force on biology, and life, to our understanding, should have no reason to not experience the effects of gravity. Interestingly, there appear to be specific biological mechanisms that activate in the absence of gravity, with the space environment the only location to study the effects of a lack of gravity on biological systems. Thus, in this perspective piece, biological adaptations from the cellular to the whole organism levels to the presence and absence of gravity are organized and described, as well as outlining future areas of research for gravitational biological investigations to address. Up to now, we have observed and shown how gravity effects biology at different levels. Based from these observations, there appear to be gravity-sensitive and specific pathways across biological organisms, though knowledge gaps of the effects of gravity on biology remain. Thus, here an overview of the literature is provided for context of gravitational biology research to-date and consideration for future studies, as we prepare to experience the effects of long-term microgravity, Lunar, and Martian gravity on biology through our Artemis program.